Evaluation of emotional distress in people with diabetes mellitus - Petrović, Verica; Vidaković, Vesna; Jelisavac, Ornela (Vojnosanitetski pregled, 2021)
Background/Aim. Despite the modern ways of treating diabetes mellitus (DM), a half of the patients do not achieve the optimal metabolic control, which increases a risk of complications and occurrence of emotional “burnout” of patients. The goal of the research was to determine the level of emotional distress of patients with diabetes, and the association of the level of emotional distress with sociodemographic traits and the disease characteristics. Methods. The research was conducted from 01.01.2016. to 04.30.2016. in the Comunity Health Center in Banja Luka. The research was conducted in a group of 113 randomly selected patients (63 men, 50 women) with diabetes, with an average age of 63.93 years. A majority of respondents have type 2 DM (91.12%). The Problem Areas in Diabetes Questionniare (PAID) was used in the research. Another questionnaire used contained questions related to sociodemographic traits (sex, age, education), and disease traits (type of DM, duration of the illness, types of therapy that the patient uses in the treatment of DM, the value of hemoglobin A1c (HbA1c) over the last three months, the presence of microvascular complications). Results. According to the total score of the PAID questionnaire, 64 (56.6%) respondents had a moderate level of emotional distress. The level of emotional distress is higher in the group with a higher HbA1c values, but without a statistically significant difference compared to the group with the achieved goal HbA1c values. Two-thirds of respondents with microvascular complications manifest a moderate level of distress. The association between occurrence of distress with the occurrence of microvascular complications was confirmed. Conclusion. More than a half of patients with DM have an elevated level of distress of a moderate degree, and two-thirds of patients with DM with the microvascular complications have an elevated level of distress of a moderate degree, which indicates the importance of interdisciplinary cooperation of endocrinologists, vascular surgeons and psychiatrists.
Keywords: diabetes mellitus; stress, psychological; glycated hemoglobin a; surveys and questionnaires.